WHAT MAKE THE AGRICULTURE SECTOR NOT ATTRACT THE YOUTH? - wibowo, arif andri; Suharno, Suharno; Alfarisy, Muhammad Farid (TRIKONOMIKA, 2024)
To ensure strong food security, regeneration becomes important and plays a real economic role. This research analyzes the influence of parents' expectations, the area of land owned by parents, technology, and the type of livestock business on young people’s interest in becoming farmers in Cilongok District, Banyumas Regency. The sample consisted of 60 young people analyzed using multiple linear regression analysis. the results show that the parent's expectations and the area of land owned by parents and technology influence the youth's interest in becoming farmers. At the same time, the type of farming variable did not affect the youth's interest in becoming farmers while the type of farming does not. These results show that to ensure farmer regeneration, strong encouragement is needed to ensure welfare, family motivation, and the role of technology in the agricultural sector. Therefore, support from all elements of society is needed to ensure the regeneration of farmers.